Antimicrobial Susceptibility Profiles of Human Campylobacter jejuni Isolates and Association with Phylogenetic Lineages - Cha, Wonhee; Mosci, Rebekah; Wengert, Samantha L.; Singh, Pallavi; Newton, Duane W.; Salimnia, Hossein; Lephart, Paul; Khalife, Walid; Mansfield, Linda S.; Rudrik, James T.; Manning, Shannon D. (Frontiers in Microbiology, 2016)
Campylobacter jejuni is a zoonotic pathogen and the most common bacterial cause of human gastroenteritis worldwide. With the increase of antibiotic resistance to fluoroquinolones and macrolides, the drugs of choice for treatment, C. jejuni was recently classified as a serious antimicrobial resistant threat. Here, we characterized 94 C. jejuni isolates collected from patients at four Michigan hospitals in 2011 and 2012 to determine the frequency of resistance and association with phylogenetic lineages. The prevalence of resistance to fluoroquinolones (19.1%) and macrolides (2.1%) in this subset of C. jejuni isolates from Michigan was similar to national reports. High frequencies of fluoroquinolone-resistant C. jejuni isolates, however, were recovered from patients with a history of foreign travel. A high proportion of these resistant isolates were classified as multilocus sequence type (ST)-464, a fluoroquinolone-resistant lineage that recently emerged in Europe. A significantly higher prevalence of tetracycline-resistant C. jejuni was also found in Michigan and resistant isolates were more likely to represent ST-982, which has been previously recovered from ruminants and the environment in the U.S. Notably, patients with tetracycline-resistant C. jejuni infections were more likely to have contact with cattle. These outcomes prompt the need to monitor the dissemination and diversification of imported fluoroquinolone-resistant C. jejuni strains and to investigate the molecular epidemiology of C. jejuni recovered from cattle and farm environments to guide mitigation strategies.